POLA HIDUP SEHAT DAN RELEVANSINYA DENGAN IBADAH PERSPEKTIF PENDIDIKAN ISLAM - Muhammad Raisa Attansyah; Sigit Dwi Laksana; Lilis Sumaryanti (Universitas Islam Lamongan, 2023)
Recently, the theme of health has made a reappearance. This is backed by implementing new habits (the new normal) after a pandemic ravaged the globe. This article discusses the relationship between the values of Islamic religious education and healthy lifestyle habits derived from the Qur'an and the hadith of Muhammad. The method employed is library research, which entails gathering and analyzing data from books or writings pertinent to the debate as primary and secondary sources. The study suggests a connection between Islamic religious ideals and a healthy lifestyle. Following what world health experts have explained, proper health is balanced between physical and mental (spiritual) health.